2004
DOI: 10.1007/s00425-003-1180-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal synthesis of abscisic acid controls seed development and yield in Nicotiana plumbaginifolia

Abstract: The role of maternally derived abscisic acid (ABA) during seed development has been studied using ABA-deficient mutants of Nicotiana plumbaginifolia Viviani. ABA deficiency induced seed abortion, resulting in reduced seed yield, and delayed growth of the remaining embryos. Mutant grafting onto wild-type stocks and reciprocal crosses indicated that maternal ABA, synthesized in maternal vegetative tissues and translocated to the seed, promoted early seed development and growth. Moreover ABA deficiency delayed bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 28 publications
(35 reference statements)
4
86
0
Order By: Relevance
“…Previous studies of ABAinsensitive mutants have shown how alterations to ABA-dependent processes impact seed maturation, dormancy, and embryo growth (Cheng et al, 2002;Frey et al, 2004). To investigate whether the ABA deficiency in aba1-7 affects the regulation of carotenoid biosynthetic and degradation genes, the expression of 50 genes from four pathways (MEP, carotenoid biosynthesis and degradation, and ABA synthesis) was assessed in the ABA-insensitive mutant abi5-7, a major ABI locus impacting developing seed (Supplemental Table S9; Finkelstein and Lynch, 2000;Bensmihen et al, 2002;Brocard et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of ABAinsensitive mutants have shown how alterations to ABA-dependent processes impact seed maturation, dormancy, and embryo growth (Cheng et al, 2002;Frey et al, 2004). To investigate whether the ABA deficiency in aba1-7 affects the regulation of carotenoid biosynthetic and degradation genes, the expression of 50 genes from four pathways (MEP, carotenoid biosynthesis and degradation, and ABA synthesis) was assessed in the ABA-insensitive mutant abi5-7, a major ABI locus impacting developing seed (Supplemental Table S9; Finkelstein and Lynch, 2000;Bensmihen et al, 2002;Brocard et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Suberin layers also cover dormant buds in potato, and the winter dormant buds of woody perennials suggest a general importance in generating the optimal internal environment for dormant plant cells. Suberization is promoted by the dormancy-inducing hormone ABA (Barberon et al, 2016), which is synthesized by the mother plant and present at increased concentrations in seeds set at low temperature (Frey et al, 2004;Kendall et al, 2011). Therefore, suberin biosynthesis may be an important adaptation for dormancy in multiple plant structures in addition to seeds.…”
Section: Discussionmentioning
confidence: 99%
“…The endogenous ABA levels in seed vary remarkably at each developmental stage (Karssen et al, 1983;Groot et al, 1991;Frey et al, 2004;Gazzarrini et al, 2004;Setha et al, 2004). In Arabidopsis, ABA is accumulated in immature siliques most abundantly at 10 DAF, and decreases gradually thereafter.…”
Section: Roles Of Cyp707as During Seed Developmentmentioning
confidence: 99%